Pemanfaatan Tabung Freon sebagai Komponen Utama Mesin Pemecah Tempurung Kemiri (Aleurites moluccana) - Iikwanto Lasimpala; Mustofa; Siradjuddin Haluti (Universitas Islam Raden Rahmat, Malang, 2024)
Candlenut is a plantation crop that is rich in benefits and uses. The increasing need for benefits and uses certainly has an impact on increasing production. Increased production must be supported by adequate technology. The technology applied must take into account local environmental conditions and the availability of raw materials. Many tools sometimes have no economic value but can be used as the main components of agricultural machinery and equipment, such as freon cylinders. This research aims to test the suitability of freon tubes as the main component for making candlenut crushing machines. The design results show that the freon tube can act as a candlenut crushing machine. However, the performance of this machine was not optimal because there were still a lot of crushed candlenuts. Apart from that, there are still candlenuts that escaped. Therefore, it is necessary to develop this machine to increase its productivity and performance.